Facile Synthesis, spectral characterization and biological evaluation of metal complexes comprising (1-hydroxynaphthalen-2-yl)methyleneamino)cyclohexylimino)methyl)naphthalen-1-olSchiff base ligand and assessing chemopharmacetical properties (Indian Journal of Chemistry (IJC), 2024)
AbstractThis work particularize a series of transition metal complexes such as Mn, Fe, Co, Ni, Cu and Zn, have been synthesized fromnewly synthesized bidentate Schiff base ligand namely (1-hydroxynaphthalen-2-yl)methyleneamino)cyclohexylimino)methyl)naphthalen-1-oland anticipated to evaluate the chemo pharmaceuticalproperties of metal complex.The Schiff base ligand and corresponding transition metal complexeshave been characterized by spectral studies such as elemental analysis, UV-Vis, FT-IR, 1HNMR, 13C NMR spectroscopy and ESI mass spectrometry.Schiff base metal complexes have been screened for their in-vitro antimicrobial activities against bacterial and fungal strains in order to prove their biological activity.The theoretical molecular docking studies revealed the existence of favorable interaction between biomolecule and synthesized complexes. Outcome of the investigation proved that the transition metal complex exhibited prominent activity towards MCF17 breast cancer tumor cell lines and therefore appropriate to design anew therapeutic chemopharmaceuticals with vital applicability and good values of antiproliferative activity. Keywords: Antiproliferative activity; Antimicrobial Chemopharmaceuticals; Moleculardocking; Schiff base;